2022
DOI: 10.3390/ijms231911084
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Maladaptive Effects of Binge Drinking on Circadian Gene Expression

Abstract: Previous studies (1) support a role of circadian genes in regulating alcohol intake, and (2) reveal that harmful alcohol use alters circadian rhythms. However, there is minimal knowledge of the effects of chronic alcohol processes on rhythmic circadian gene expression across brain regions important for circadian biology and alcohol intake. Therefore, the present study sought to test the effects of chronic binge-like drinking on diurnal circadian gene expression patterns in the master circadian pacemaker (SCN),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…It should be mentioned that published evidence indicates that diurnal rhythms in the expression of clock genes may differ within the same species, and could be affected by the analysed tissue and/or genetic differences. A study in high drinking in the dark-1 (HDID-1) mice (Grigsby et al, 2022), which revealed distinct diurnal circadian gene expression patterns in various brain regions, including the SCN, ventral tegmental area, and nucleus accumbens. These patterns diverged not only from each other but also from previous studies on mice, such as the work of Zhang et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that published evidence indicates that diurnal rhythms in the expression of clock genes may differ within the same species, and could be affected by the analysed tissue and/or genetic differences. A study in high drinking in the dark-1 (HDID-1) mice (Grigsby et al, 2022), which revealed distinct diurnal circadian gene expression patterns in various brain regions, including the SCN, ventral tegmental area, and nucleus accumbens. These patterns diverged not only from each other but also from previous studies on mice, such as the work of Zhang et al (2014).…”
Section: Discussionmentioning
confidence: 99%